Associations between genomic ancestry, genome size and capitula morphology in the invasive meadow knapweed hybrid complex (Centaurea × moncktonii) in eastern North America. Issue 5 (23rd August 2019) - Lachmuth, Susanne; Molofsky, Jane; Milbrath, Lindsey; Suda, Jan; Keller, Stephen R
Abstract: Plant invasions are prime opportunities for studying hybridization and the nature of species boundaries, but hybrids also complicate the taxonomic treatment and management of introduced taxa. In this study, we use population genomics to estimate the extent of genomic admixture and test for its association with morphology and genome size in a hybrid complex of knapweeds invasive to North America: meadow knapweed ( Centaurea × moncktonii ) and its parental species ( C. jacea and C. nigra ). We sampled 20 populations from New York and Vermont, USA, and used genotyping by sequencing to identify single nucleotide polymorphisms in order to estimate genome-wide ancestry and classify individuals into hybrid genotype classes. We then tested for association between degree of genomic introgression and variation in a subset of traits diagnostic for the parental taxa, namely capitula morphology and monoploid genome size. Genomic clustering revealed two clearly defined lineages, as well as many admixed individuals forming a continuous gradation of introgression. Individual assignments to hybrid genotype classes revealed many advanced generation intercrosses and backcrosses, suggesting introgression has been extensive and unimpeded by strong reproductive barriers between taxa. Variation in capitula traits between the two unadmixed, presumed parental, lineages exhibited continuous, and in some cases transgressive, segregation among introgressed hybrids. Genome size was also divergent between lineages, although advanced generation hybrids had smaller genomes relative to additive expectations. Our study demonstrates deep introgression between the porous genomes of a hybrid invasive species complex. In addition to strong associations among genomic ancestry, genome size and morphology, hybrids expressed more extreme phenotypic values for capitula traits and genome size, indicating transgressive segregation, as well as a bias towards smaller genomes, possibly due to genomic downsizing. Future studies will apply these results to experimentally test how introgression, transgressive segregation and genome size reduction interact to confer invasiveness. Abstract : Hybridization is thought to be a primary trigger underlying plant invasiveness, yet identifying hybrids and differentiating them from their parental species presents formidable challenges. Here, we present a multifaceted analysis of the invasive meadow knapweed complex that unravels the genetic make-up of hybrid populations in North America using DNA sequencing to infer the genomic ancestry of individuals, and associating ancestry with variation in floral traits and genome size. We find extensive genomic evidence of hybrids, with significant but incomplete correspondence with floral traits and genome size. Our results highlight the widespread yet often cryptic nature of hybridization in plant invasions.